Alternative Soundproof Material to Reduce Noise HVAC Round Duct System (Rockwool and Bamboo Fiber) - Mohd Zubir, Muhammad Zariq Ikhwann; Wan Abdul Rahman, Wan Mohd Wardi (Progress in Engineering Application and Technology, 2021)
Rockwool is one of the materials that usually used as exterior sound insulation on air duct for HVAC in order to overcome break-out noise problem. However, this material is catogorized as non-biodegradable material and contribute to global warming. The purpose of this study was to investigate the acoustical properties of rockwool and Betung bamboo (Dendrocalamus Asper) fiber as new material for sound insulation. The acoustic parameters were measured are the sound absorption coefficient (SAC) and sound transmission loss (STL). The bamboo fiber of two different thickness (25 mm and 50 mm) with density of 60 kg/m3 and 120 kg/m3 respectively, while the rockwool also two different thickness (25 mm and 50 mm) with same density of 40 kg/m3 were tested in this study. The SAC value was determined using impedance tube at low and high frequencies guided by EN ISO 10534-2:2001, while the STL was measured in a reverberation room by following EN ISO 140-3:1995. The results showed that bamboo fiber samples absorbed more sound energy compared to rockwool samples at both low and high frequency region. Maximum SAC value obtained by 50 mm thick and 120 kg/m3 density of bamboo fiber sample at low frequency is 0.99 at 1250 Hz and 1350 Hz, while at high frequency, the maximum absorption was also obtained by 50 mm thick bamboo fiber sample with SAC value of 0.99 at 4000 Hz. The results also showed that bamboo fiber samples having higher STL value than rockwool samples. Maximum STC value of bamboo fiber is 72 dB at 4000 Hz. This results indicated that thicker and denser samples absorbed and eliminated more sound energy compared to thinner and less dense samples. In conclusion, bamboo fiber is highly potential to be used as raw material for sound absorption material replacing synthetic materials since these fiber are renewable, cheaper and give less negative effect to human health.